Influência de diferentes estágios sucessionais na composição e riqueza de liquens na caatinga - Mendonça, Cléverton de Oliveira (2014)
The successional processes in tropical forests follow a progression of stages during which forests have a gradual enrichment of species and an increase in structural and functional complexity. Stochastic actions resulted from the behaviour of the population s components and species define forest succession, where biotic and abiotic factors lead the ecological diversity strategies in a community according to local and regional environmental filters. Lichens are organisms with complex relationship within successional forest because they respond to spatial and temporal factors, and at the same time, are bioindicators of environmental quality. In this context, the present study aims to investigate the richness and species composition of corticicolous lichens along a gradient of forest succession in the Caatinga biome, and verify the possibility of using functional traits of lichens as indicators of successional stages of this type of vegetation. The study was undertaken in three areas of different successional stages in the Caatinga from Sergipe semiarid, in two municipalities. A total of 1460 samples were collected, distributed between the initial, intermediate and advanced stage areas. After the analysis, 119 species were identified, comprising 17 families and 47 genera. The richness differs between stages of succession, where the highest values are for the initial stage, followed by intermediate and later stages. Among the sampled environmental factors, the pH of the rainy season is the one that significantly affects species richness. Regarding species composition, there is a clear separation of stages, where the advanced stage differs from the initial and intermediate and are influenced by parameters such as bark pH, DAP of the tree, brightness, and elevation. The beta diversity is higher for the advanced stage, which has a more heterogeneous composition than the initial and intermediate, which share species among themselves. The functional traits presents a noticeable variation in the abundance and are bioindicators of stages of succession. Results show that the community of lichens respond to natural succession and is influenced by biotic and abiotic factors. Therefore, it is expected that this work will contribute to enhance the ecological knowledge of lichens in the Caatinga, serving as the starting point for complementary and innovative research that contributes to the conservation of this ecosystem.